P2Y6 Receptor-Mediated Spinal Microglial Activation in Neuropathic Pain - Jiang Bian; Ying Zhang; Yan Liu; Qun Li; Hai-bin Tang; Qing Liu (Pain Research and Management)
Objective. To explore the role of purine family member P2Y6 receptors in regulating neuropathic pain (NP) via neuroinflammation in the spinal cord. Methods. Chronic constriction injury of the sciatic nerve (CCI) of NP was classic in setting up models on Sprague-Dawley (SD) rats. Experiments were performed on rats with sham surgery, CCI, CCI + MRS2578 (a P2Y6 receptor antagonist), and UDP (a P2Y6 receptor agonist). The hyperalgesia intensity was mirrored by paw withdrawal threshold (PWT) and thermal withdrawal latency (TWL). Immunofluorescence staining and western blot were used to evaluate activated microglial marker Iba-1. Enzyme-linked immunosorbent assay (ELISA) was used to access levels of IL-6. Conventional reverse transcription polymerase chain reaction (RT-PCR) and western blot analysis were used to detect the expression of P2Y6 mRNA and activation of JAK/STAT signaling. Results. Among all groups, CCI caused decreased PWT and TWL compared to sham surgery, meaning a successful establishment of the NP model. These decreased values of PWT and TWL tests could be prevented by intraperitoneally injected MRS2578 and enhanced by UDP administration. Similarly, CCI induced increase of Iba-1 protein, P2Y6 mRNA expression, and circulating IL-6 secretion, as well as increased JAK2/STAT3 mRNA expression and phosphorylating modification in spinal cord tissues could also be diminished by MRS2578 treatment and exacerbated by UDP. Conclusions. These findings indicated the crucial role of the P2Y6 receptor in modulating the microglial and inflammatory responses in the process of NP in vivo. Results from this study would provide insights into targeting the P2Y6 receptor to treat NP in the near future.